'Sea songs and shanties' workshop presented at the 1967 Moreton Bay Folk Festival at Brisbane, Queensland in Queensland Folk Federation collection - Queensland Folk Federation (1967)
Folkloric recording
Music: singing: A-roving -- Lowlands -- Nancy of Yarmouth -- Old Stormy's gone -- General Taylor -- The banks of Sacramento (Blow boys blow) -- The black ball line -- The trim ring ducksie.
Recordings of folk festivals, workshops, concerts, performances and recitations by various artists collected by the Queensland Folk Federation throughout the mid 1960s to the late 1980s. Included in this collection are select radio folk programmes.
Recorded on June 3, 1967 at Brisbane, Qld.
Digital master available
Keywords: Sea songs; Folk festivals -- Queensland